Soil health connection to water conservation - Coughlin, Gabriella, speaker; Colorado State University. Extension, producer (Colorado State University. Libraries, 2022)
An evolution of soil and water conservation in the Middle Rio Grandy Valley.
Presented at the 40th annual Southern Rocky Mountain Agriculture Conference on Februrary 1-3, 2022 at Ski Hi Park & McMullen Building in Monte Vista, Colorado.
Title and date taken from website.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Rio Grande Valley (Colo.-Mexico and Tex.); Rio Grande Watershed (Colo.-Mexico and Tex.); Soil management; Soil conservation; Water conservation